SINTESIS FOTOKATALIS NANOPARTIKEL PERAK (NPAg) DENGAN BIOREDUKTOR EKSTRAK DAUN SIRSAK (Annona muricata L.) DAN APLIKASINYA DALAM FOTODEGRADASI ZAT WARNA CONGO RED - Saraswati, A.A. Sagung Diah; Suprihatin, Iryanti Eka; Gede Bawa, I Gusti Agung (CAKRA KIMIA (Indonesian E-Journal of Applied Chemistry); Vol 12 No 2 (2024): Cakra Kimia (Indonesian E-Journal of Applied Chemistry), 2024)
ABSTRACT: The rapid development of the textile industry has provided many benefits, but also has a negative impact, especially on environmental pollution, as a result of poor waste management. One of the dye wastes that are difficult to degrade in nature is Congo Red dye waste. This study aims to synthesize silver nanoparticles using a bioreductant of soursop leaf extract which will be used to degrade Congo Red dye. The synthesis of NPAg was carried out on variations in the volume of soursop leaf aqueous extract with AgNO 3 solution, namely 1:9; 2:8; 3:7; 4:6; 5:5, and carried out at 40, 50, and 60°C. identification of NPAg formed using UV-Vis spectrophotometry and Particle Size Analyzer (PSA). The results showed that the NPAg formed at the ratio of the volume of soursop leaf water extract to AgNO 3 solution 3:7 at a temperature of 40°C gave the best results, because it has a maximum wavelength of 433.40 nm, size 49.30 nm, has a Polydispersity Index (IPd) value is 0.232, and the zeta potential value is -6.41 mV. Photodegradation of Congo Red with NPAg was carried out under optimum conditions, namely 1 mL of NPAg volume, 3 hours of degradation time, and pH 2 capable of degrading Congo Red dye by 98.70%.